"Have you read my comments? It is not noticeable. Change!" An analysis of feedback given to students who have failed examinations. Issue 2 (17th February 2018) - Sellbjer, Stefan
Abstract: The aim of this article is to examine what characterises feedback regarding the group of students who receive the most comments compared to the rest of the students, all failing at least one task. Could it be that teachers comment differently on the most underperforming students? The empirical material consists of feedback handed out to students following a teacher training programme and is examined on the basis of a descriptive analytical investigation. The analysis is based on four methods: the type of errors made, the number of times a student makes the same mistake, what kind of feedback was provided and 'de-motivational' comments. Underperforming students receive more feedback on their choice of relevant literature and on the qualification of the answer. They also receive substantially more 'de-motivational' feedback, as well as a higher proportion of the most negative and disparaging comments. A recommendation for further research is to separate feedback that is related to the qualities of the students' work from what characterises the teacher's comments, whatever aspect of the work is being commented on.